2013
DOI: 10.1007/s11325-013-0915-3
|View full text |Cite
|
Sign up to set email alerts
|

Adenotonsillectomy and orthodontic therapy in pediatric obstructive sleep apnea

Abstract: Our data demonstrate that both treatments help to improve OSA, and a multidisciplinary approach to treatment is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
30

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 32 publications
0
51
0
30
Order By: Relevance
“…Ethmoid growth stops by the age of 2 years. It is known that maxillary narrowness is a factor of OSA in children [15,16], which may be treated by orthodontic maxillary expansion combined or not with adenotonsillectomy [17]. The present study explicitly highlighted maxillo-palatine narrowness after height [14].…”
Section: [ ( F I G _ 4 ) T D $ F I G ]mentioning
confidence: 53%
See 1 more Smart Citation
“…Ethmoid growth stops by the age of 2 years. It is known that maxillary narrowness is a factor of OSA in children [15,16], which may be treated by orthodontic maxillary expansion combined or not with adenotonsillectomy [17]. The present study explicitly highlighted maxillo-palatine narrowness after height [14].…”
Section: [ ( F I G _ 4 ) T D $ F I G ]mentioning
confidence: 53%
“…5 show the smallest transverse UA section. For the patient on the left, a ou pas, à l'adenotonsillectomie [17]. L'etude presente a souligne explicitement l'etroitesse maxillopalatine apres ajustement pour la taille chez les adultes souffrant d'AOS, comme cela a dejà ete suggere dans des etudes cephalometriques anterieures.…”
Section: [ ( F I G _ 4 ) T D $ F I G ]unclassified
“…11,12,14,15 Similarly, the studies that have investigated the converse, i.e. the effect of no treatment, have also included a wide age range, 14,[16][17][18] were only conducted in older children, 12,17,[19][20][21] had short or variable follow-up periods, 19 or did not use the gold standard of overnight polysomnography but relied on parental questionnaires to assess SDB severity.…”
Section: Brief Summarymentioning
confidence: 99%
“…Villa MP [31] observed that rapid maxillary expansion can be used to treat apnea in children with malocclusion and its effects persist until 24 months after the end of the intervention [31]. Barreto and collaborators (2014) selected 52 children with OSAS and divided them into 3 groups [32]. Those with a milder disease were referred for MRA and those with a more severe disease were referred for amygdala and adenoid surgery.…”
Section: Rapid Maxillary Expansionmentioning
confidence: 99%